Spatially Resolved Quantification of Gadolinium(III)‐Based Magnetic Resonance Agents in Tissue by MALDI Imaging Mass Spectrometry after In Vivo MRI1. (16th February 2015) - Aichler, Michaela; Huber, Katharina; Schilling, Franz; Lohöfer, Fabian; Kosanke, Katja; Meier, Reinhard; Rummeny, Ernst J.; Walch, Axel; Wildgruber, Moritz
Abstract: Gadolinium(III)‐based contrast agents improve the sensitivity and specificity of magnetic resonance imaging (MRI), especially when targeted contrast agents are applied. Because of nonlinear correlation between the contrast agent concentration in tissue and the MRI signal obtained in vivo, quantification of certain biological or pathophysiological processes by MRI remains a challenge. Up to now, no technology has been able to provide a spatially resolved quantification of MRI agents directly within the tissue, which would allow a more precise verification of in vivo imaging results. MALDI imaging mass spectrometry for spatially resolved in situ quantification of gadolinium(III) agents, in correlation to in vivo MRI, were evaluated. Enhanced kinetics of Gadofluorine M were determined dynamically over time in a mouse model of myocardial infarction. MALDI imaging was able to corroborate the in vivo imaging MRI signals and enabled in situ quantification of the gadolinium probe with high spatial resolution.